Toward a Balanced Scorecard Healthcare Organization : A Case Study on Assessing Performance Measurement Progress at Government Hospital - Hii, Juliana Li Li (2004)
This case study examined and described the progress of the existing performance measurement at a government hospital. Specifically the objectives of the study were to gain a better understanding of the current measurement system and with the aid of strategic balanced scorecard (BSC) approach, help in identifying possible self-improvement to the system. Beside that, the study also tried to answer the question on why the hospital management continued with the practice of the current system and revealed the level of BSC adoption at the organizational level if any. For this study 50 sets of questionnaire consisted of 50 items measured with 5 point Likert scale was distributed to the identified respondents as the main method of collecting quantitative data, while 7 top management staffs were willing to be interviewed for the qualitative data. Out of the figure, only 30 sets of completed questionnaire were used and analyzed with the SPSS simple descriptive statistic program, while qualitative data came from the interviewees. It was found that the hospital current practice of performance measurement is well within a middle band performance with overall score of about 223. This showed a positive note of development and a good beginning in re-engineering hospital approach to its measurement system. However, the result indicated that hospital was still weak in employee related measures and certain suppliers’ measures and at the same time having strength in finance, operation and product/service quality measures. Category of measures used by the hospital was quite balanced, namely finance, operation/activity, quality, personnel and safety, while productivity and efficiency are generally emphasized in these measurements. Interview result also showed that management had no plan to make changes to its current practice for time being due to factors such as benefit of practice, time and effort and influence of management commitment. Also, officially there was no level of balanced scorecard (BSC) adoption at the hospital but there were similarity of BSC elements being practiced at the organization. Hence, this study proposed improvement in certain area of weakness like feedback, monitoring of frequencies and adoption of the real BSC approach towards a more balanced organization.